PENGARUH FINANCIAL LITERACY, HERDING, RISK PERCEPTION TERHADAP KEPUTUSAN INVESTASI PADA MAHASISWA AKUNTANSI UNIVERSITAS PAMULANG ANGKATAN 2020-2021 - Berlian Savira Pratidina; Anggun Anggraini (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to investigate the influence of financial literacy, herding behavior, and risk perception on investment decisions among accounting students at Pamulang University from the 2020 - 2021 cohort. The research is of a quantitative (primary) nature and adopts a conclusive causal approach. The sample comprises 105 students, selected using Convinience Sampling. Data were collected through questionnaires. The data analysis technique employed is quantitative in nature, utilizing the IBM SPSS 27 software. The research findings, based on partial tests using the T-test, indicate that (1) financial literacy has a significant impact on investment decisions, (2) herding behavior has a significant impact on investment decisions, and (3) risk perception significantly affects investment decisions. According to the simultaneous test using the F-test, it can be concluded that financial literacy, herding behavior, and risk perception collectively have a significant impact on investment decisions.